CURVA DE CRESCIMENTO DE CALOS DE MARACUJAZEIRO NATIVO - Carvalho, Milene Alves de Figueiredo; Paiva, Renato; Vargas, Daiane Peixoto; Silva, Luciano Coutinho; Nogueira, RaÃrys Cravo (REVISTA DE AGRICULTURA, 2016)
CURVA DE CRESCIMENTO DE CALOS DE MARACUJAZEIRO NATIVO